2013 IEEE/ASME International Conference on Advanced Intelligent Mechatronics 2013
DOI: 10.1109/aim.2013.6584350
|View full text |Cite
|
Sign up to set email alerts
|

Active robot hand compliance using operational space and Integral Sliding Mode Control

Abstract: This paper establishes a novel approach of robust active compliance control for a robot hand via an Integral Sliding Mode Controller (ISMC). The ISMC allows us to introduce a model reference approach where a virtual mass-spring damper system can be used to design a compliant control. In order to allow for practical grasping, we consider the shape of the object to be grasped. Hence, the work exploits a grasping technique via Cylindrical and Spherical coordinate systems due to their simplicity and geometric suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Hence, we also extend significantly over our own recent work on compliant grasping (Jalani et al (2013) 11 ; Jalani et al…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Hence, we also extend significantly over our own recent work on compliant grasping (Jalani et al (2013) 11 ; Jalani et al…”
Section: Introductionmentioning
confidence: 87%
“…The grasping task needs to guarantee that the fingers sufficiently surround the object, staying in good contact and creating a suitable ergonomicsinspired posture 10 . As a result of such analysis, the authors of this paper suggested for hand positioning for grasp and for grasping an object-based coordinate system (see early ideas in Jalani, Mahyuddin, Herrmann & Melhuish (2013) 11 and Jalani, Herrmann & Melhuish (2011) 12 ); hence, this choice of coordinate system focuses on the object shape. Thus, the control is carried out in relation to the object shape rather than in a global Cartesian coordinate frame.…”
Section: Introductionmentioning
confidence: 99%
“…The sliding mode element r given by Eq. (1) is modified to introduce the compliance effect based on the external sensed force via joint torque sensors (Jalani et al, 2013;Herrmann et al, 2014):…”
Section: Model Reference Compliance Control Using Ismcmentioning
confidence: 99%
“…A Cartesian (X, Y and Z) model reference type of ISMC compliant scheme is simulated for 4 DOF of the humanoid BERT II robot arm 1 . Different compliance levels are produced by choosing spring constant and damping coefficients in the reference model (Jalani et al, 2013;Herrmann et al, 2014). The scheme will be used to address safety issues in human-robot interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation